2014
DOI: 10.3390/atmos5040914
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Programming for the Downscaling of Extreme Rainfall Events on the East Coast of Peninsular Malaysia

Abstract: Abstract:A genetic programming (GP)-based logistic regression method is proposed in the present study for the downscaling of extreme rainfall indices on the east coast of Peninsular Malaysia, which is considered one of the zones in Malaysia most vulnerable to climate change. A National Centre for Environmental Prediction reanalysis dataset at 42 grid points surrounding the study area was used to select the predictors. GP models were developed for the downscaling of three extreme rainfall indices: days with lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 80 publications
(40 citation statements)
references
References 59 publications
(51 reference statements)
1
39
0
Order By: Relevance
“…Several authors such as Pour et al [78] reported that in general, extreme events frequently occur at the micro scale, therefore, gridded data may not have the capability to capture those phenomena precisely at point level. Schneider et al [79] argued that extreme events in the gridded data at micro or small scale can only be captured precisely with a greater number of observed stations or dense network of stations over an area.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors such as Pour et al [78] reported that in general, extreme events frequently occur at the micro scale, therefore, gridded data may not have the capability to capture those phenomena precisely at point level. Schneider et al [79] argued that extreme events in the gridded data at micro or small scale can only be captured precisely with a greater number of observed stations or dense network of stations over an area.…”
Section: Discussionmentioning
confidence: 99%
“…Coulibaly () used GP to develop models to downscale reanalysis data to daily temperature, Pour et al . () used GP to downscale reanalysis data to daily precipitation indices and Sachindra and Perera () employed GP to downscale reanalysis data to monthly precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…In several statistical downscaling studies, GP has been used for determining relationships between the predictors and the predictand, and simultaneous identification of a subset of potential predictors. Coulibaly (2004) used GP to develop models to downscale reanalysis data to daily temperature, Pour et al (2014) used GP to downscale reanalysis data to daily precipitation indices and employed GP to downscale reanalysis data to monthly precipitation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The artificial neural network can approximate nonlinear relations between predictors and predictands and their derivatives without prior knowledge of a specific nonlinear function (Gupta et al, 2014), which is helpful for making accurate forecasts of highly nonlinear climate systems (Schoof, 2013). A growing number of computational learning algorithms including tree-based methods (Goyal et al, 2012), genetic programming (Pour et al, 2014), support vector machines (Tripathi et al, 2006), and relevance vector machines (Ghosh and Mujumdar, 2008) were developed as well. Classification methods that were exploited based on expert systems (Dong et al, 2011(Dong et al, , 2012(Dong et al, , 2013(Dong et al, , 2014c, fuzzy rules (Bárdossy et al, 2002;Khan and Valeo, 2016), stepwise cluster analysis (Wang et al, 2013), and selforganizing maps (Huva et al, 2015) were widely applied within a context of downscaling.…”
Section: Introductionmentioning
confidence: 99%